Assistive and Therapeutic Effects of Amplification for Auditory Processing Disorder - Keith, William J.; Purdy, Suzanne C. (Seminars in Hearing, 2014)
Studies of the effects of amplification with remote microphone hearing aids for children with auditory processing disorder or dyslexia consistently show therapeutic as well as assistive benefits from the amplification. The immediate assistive benefits include improved attention, learning, behavior and participation in class, and improved self-esteem and psychosocial development. The long-term therapeutic benefits include improvements in cortical auditory evoked potential amplitudes to tone stimuli, auditory brainstem responses to speech stimuli, frequency discrimination, binaural temporal resolution, frequency pattern recognition, auditory working memory, core language, phonological awareness, and speech perception in spatially separated noise. Amplification appears to treat a wide range of auditory skills simultaneously, facilitating neuroplastic change while also providing access to the auditory world. Expert intervention to engage the support of teachers is a critical element in achieving successful outcomes. Children treated with remote microphone hearing aids may not require long-term amplification.
Keywords: Auditory processing; remote microphone hearing aids; FM systems; auditory neuroplasticity; dyslexia